Is everyone in class in agreement and why (not)? Using student and teacher reports to predict within-class consensus on goal structures. (February 2021) - Bardach, Lisa; Yanagida, Takuya; Morin, Alexandre J.S.; Lüftenegger, Marko
Abstract: Students in the same class can differ considerably in their perceptions of teaching quality, but little is known about the drivers of this lack of agreement. In this study, we relied on within-class consensus as a measure of agreement in students' perceptions and explored both student-reported predictors (Sample 1) and teacher-reported predictors (Sample 2) of consensus in students' ratings of six goal structures dimensions (task, autonomy, recognition, grouping, evaluation, time). Classroom-level results from multi-level models indicated that student-perceived differential teacher treatment negatively predicted consensus regarding evaluation, as well as achievement heterogeneity, whereas instructional clarity positively predicted consensus for recognition, grouping, and evaluation, as well as class-average achievement (Sample 1). Mediating effects of achievement heterogeneity and achievement were not statistically significant. In Sample 2, negative effects of teacher-reported emotional exhaustion and teaching-related anxiety on consensus were observed for several dimensions. Teaching-related enjoyment had no effect. Highlights: Students in the same class can differ considerably in their perceptions of teaching quality. Need to identify predictors of variability in perceptions. Teachers should increase the clarity of instruction to reduce variability in perceptions. Differential teacher treatment contributes to higher variability in perceptions. If teachers report higher emotional exhaustion and anxiety, students agree less in perceptions.